Grid Impact of Battery Swapping Station for Electric Two-Wheelers in Indonesia - Jamaluddin, Tisha Aditya Anggraini; Syamroni, Abdul Wachid; Husnayain, Faiz (Universitas Indonesia, 2025)
Indonesia is rapidly advancing toward electric transportation, with electric two-wheelers playing a crucial role, driven by widespread use and cost-effectiveness. While battery swapping stations (BSS) offer a practical and gap solution over charging station scenario through the stop-go schema, knockdown units and lessen upfront investment, however their unpredictable nature—stemming from random user swaps and varying battery state-of-charge (SoC)—creates dependency operational challenges, particularly for low-voltage distribution grid feeders (DGF). Hence, this article thoroughly evaluates grid impacts using a modified IEEE 9-bus system, focusing on future urban multi-source feeders in Indonesia. A stochastic simulation process for BSS operates every minute over 1440 periods, effectively capturing the near-realistic dynamics of BSS operational behavior and assessing the effects on voltage stability, lines, and transformer loadings concerning BSS integration in quasi-dynamic power flow analysis through DIgSILENT PowerFactory. The findings reveal that even a minor deployment of BSS can cause a voltage drop of up to 1.1%, a 30% increase in transformer loading, and a 100% rise in line loading, especially during peak exchangeable periods. These results highlight the need for proactive infrastructure planning and grid readiness strategies toward Indonesia’s future vision to decarbonize the transport sector into a scalable electric vehicle (EV) ecosystem.